Revascularization of Transplanted Pancreatic Islets and Role of the Transplantation Site. (8th September 2013) - Pepper, Andrew R.; Gala-Lopez, Boris; Ziff, Oliver; Shapiro, A. M. James
Abstract : Since the initial reporting of the successful reversal of hyperglycemia through the transplantation of pancreatic islets, significant research efforts have been conducted in elucidating the process of revascularization and the influence of engraftment site on graft function and survival. During the isolation process the intrinsic islet vascular networks are destroyed, leading to impaired revascularization after transplant. As a result, in some cases a significant quantity of the beta cell mass transplanted dies acutely following the infusion into the portal vein, the most clinically used site of engraftment. Subsequently, despite the majority of patients achieving insulin independence after transplant, a proportionof themrecommence small, supplemental exogenous insulin over time. Herein, this review considers the process of islet revascularization after transplant, its limiting factors, and potential strategies to improve this critical step. Furthermore, we provide a characterization of alternative transplant sites, analyzing the historical evolution and their role towards advancing transplant outcomes in both the experimental and clinical settings.